Enantioselective Synthesis of Trifluoromethylated Tertiary Thioethers through Organocatalytic Sulfa-Michael Addition of Thiols to β-Trifluoromethyl β,β-Disubstituted Enones - Wang, Yao-Feng; Wu, Shaoxiang; Karmaker, Pran Gopal; Sohail, Muhammad; Wang, Qi; Chen, Fu-Xue (Synthesis, 2015)
An organocatalytic asymmetric sulfa-Michael addition of thiols to β-trifluoromethyl β,β-disubstituted (E)-enones in the presence of 10 mol% of a cinchona alkaloid-derived thiourea catalyst provides direct and simple access to chiral trifluoromethyl tertiary thioethers in high yields and up to 76% ee.
Keywords: asymmetric catalysis; enones; Michael additions; organocatalysis; thiols; sulfides